Effect of seedling quality on growth, yield and quality of tomato (Solanum lycopersicum L.) - Nkurunziza, E.; Nyalala, S.; Umuhoza, K. N. J. (International Journal of Horticultural Science, 2022)
A two trial greenhouse experiment was carried out at Rwanda-Israel Horticulture Centre of Excellence located at Mulindi Station to evaluate seedling quality on growth, yield and quality of tomato. The seedlings were grown in different growing media and produced seedlings with varying quality indices. The growing media of peat moss 100% (T2) and sand + goat manure + carbonized rice husks 50%: 10%: 40% (T8) were revealed in seedlings with the highest mean quality indices of 31 and 28 respectively, while sand 100% (T2) presented the lowest quality indices during both trials. The transplants were planted in polybags filled with 2:1 of topsoil and kitchen manure arranged in a randomized complete block design (RCBD) with four replications. Collected data were subjected to analysis of variance and means were separated using HSD test at a 5% level of significance. The results revealed that the seedlings grown in T1 (S1) and T8 (S8) consistently presented tomatoes with better growth performance and yield. S1 and S8 produced mean yield of 93.59 and 92.35 t/ha respectively while S2 had the lowest yield with 53.86 t/ha. The fruit produced from seedlings grown in T4 (S4) had the highest mean sugar acid ratio of 5.88 but not significantly different from 5.61 and 5.44 of S1 and S8 respectively. Hence, there was a positive relationship among seedling quality and growth and yield performance of tomato but not in fruit quality.